Contraceptive practices in women with chronic medical conditions. (19th May 2021) - Hunter-Greaves, Tiffany; Medley-Singh, Natalie; Tate, Nastassia; McDaniel, Anjanette; Simms-Stewart, Donnette; Rattray, Carole
Abstract: Contraception in women with severe medical conditions is a potential measure to reduce maternal mortality. We sought to determine the contraceptive use in women with medical conditions at the University Hospital of the West Indies (UHWI) in Jamaica to determine if there is room for improvement in contraceptive use. Participants were identified from the medical out-patient departments and questionnaires administered. Two hundred and sixty females between 18 and 44 years with varied chronic medical conditions were included. Those included were systemic lupus erythematosus (SLE), diabetes, hypertension (HTN), thyroid disease, cardiac and renal disease. The total current use of contraception was 58.4%, while 41.6% were not on contraceptives. The use of barrier methods and long-acting reversible contraceptives (LARCs) was 71% and 10%, respectively. The current use of contraception in patients with sickle cell disease (SCD) was 84% ( p =.004) and in rheumatoid arthritis (RA), 14% ( p =.028). Fifty-eight (58, 24.2%) of the women were using two or more methods of contraception. There is a role for improving contraceptive use among women with medical conditions as they are at increased risk of pregnancy complications. IMPACT STATEMENT: What is already known on this subject? Women with medical comorbidities significantly contribute to both direct and indirect causes of maternal mortality. Contraception may play an integral role in reducing the risk of dying in chronically ill women; however, the use of contraception in this group is often suboptimal. What the results of this study add? This study adds to the literature that in this high-risk group, there is an underuse of long-acting reversible contraceptives, which is ideal for this population. What the implications are of these findings for clinical practice or further research? The results will provide evidence that this high-risk group of women should be targeted and counselled regarding their risk of morbidity and mortality in pregnancy as well as contraception use while their condition is optimised. From this evidence, services may be put in place in institutions, especially in low-resource settings.